Health effects from contaminant exposure in Baltic Sea birds and marine mammals: A review - Sonne, Christian; Siebert, Ursula; Gonnsen, Katharina; Desforges, Jean-Pierre; Eulaers, Igor; Persson, Sara; Roos, Anna; Bäcklin, Britt-Marie; Kauhala, Kaarina; Tange Olsen, Morten; Harding, Karin C.; Treu, Gabriele; et al. (Elsevier Ltd., 2020)
Here we review contaminant exposure and related health effects in six selected Baltic key species. Sentinel species included are common eider, white-tailed eagle, harbour porpoise, harbour seal, ringed seal and grey seal. The review represents the first attempt of summarizing available information and baseline data for these biomonitoring key species exposed to industrial hazardous substances focusing on anthropogenic persistent organic pollutants (POPs). There was only limited information available for white-tailed eagles and common eider while extensive information exist on POP exposure and health effects in the four marine mammal species. Here we report organ-tissue endpoints (pathologies) and multiple biomarkers used to evaluate health and exposure of key species to POPs, respectively, over the past several decades during which episodes of significant population declines have been reported. Our review shows that POP exposure affects the reproductive system and survival through immune suppression and endocrine disruption, which have led to population-level effects on seals and white-tailed eagles in the Baltic. It is notable that many legacy contaminants, which have been banned for decades, still appear to affect Baltic wildlife. With respect to common eiders, changes in food composition, quality and contaminant exposure seem to have population effects which need to be investigated further, especially during the incubation period where the birds fast. Since new industrial contaminants continuously leak into the environment, we recommend continued monitoring of them in sentinel species in the Baltic, identifying possible effects linked to climate change, and modelling of population level effects of contaminants and climate change.
Keywords: PCBs; Polychlorinated biphenyls; Baltic Sea; POPs; Persistent organic pollutants; Organochlorine pesticides; OCP; exposure; Biological effects; Contaminants